Occupational Health and Safety Management System ISO 45001 as a mechanism to enhance the health of workers in economic institutions - Meyada, BELAICHE; Abdelghani, REMITA; Salah, FERROUM Mohamed; Samir, AMMARI (Journal of Ecohumanism, 2026)
The Occupational Health and safety of workers is one of the issues that has received increased attention recently, as a result of the registration of many injuries and accidents related to the health of workers, especially those related to occupational hazards such as physical and psychological diseases, accidents and work injuries, which often led to the loss of the human element. Here, the urgent need for economic institutions for the Occupational Health and Safety System ISO 45001 has emerged as a result of the registration of many injuries and accidents related to the Occupational Health and safety of workers, especially those related to occupational hazards such as physical and psychological diseases, accidents and work injuries, which often led to the loss of the human element. Therefore, this research paper highlights the importance of the application of the ISO 45001 Occupational Health and safety system by economic institutions, as its application achieves many advantages and positive results, the most important of which are: enhancing the mental and physical health of employees, which reflects positively on their performance or productivity at work on the one hand, and on the other hand achieves their job satisfaction.